SPEAKING PERFORMANCE PATTERN OF LECTURERS AND PRACTITIONERS IN TEACHING PRACTITIONERS PROGRAM AT UNIVERSITAS HKBP NOMMENSEN - Sinaga, Nenni Triana; Lestari, Febrika Dwi; Octavia, Yessy; Surbakti, Mariana Br; Lubis, Rointan (TELL - US JOURNAL, 2025)
This study aims to find the speaking performance pattern of lecturer and practitioner in practitioners program at Universitas HKBP Nommensen. This study employs the education anthropolinguistic approach with descriptive qualitative research. Observation and open-ended interview was used in collecting data. The data is the utterances of practitioner and lecturer in teaching learning process that analyzed with interactive models, namely: data condensation, data display, and drawing conclusion/verifying. The research result show that the pattern of speaking performance strategies influences the teaching effectiveness. This result advances an integrated understanding of pedagogical theory in conjunction with speakers' experiences, focusing on developing speaking professionalism. Therefore, the novelty of this research is improving the overall quality of these programs by equipping educators with effective communication competencies, thereby fostering more engaging, impactful, and professional teaching practices.